47.9k views
3 votes
Plzz help really fast

Plzz help really fast-example-1

2 Answers

4 votes

Answer:

the answer is 32

Explanation:

User Lucas Van Dongen
by
5.4k points
5 votes

Answer:

32

Explanation:

Let's do it step by step:


-16(-5(1)/(2) / 2(3)/(4)) = -16((-5(1)/(2))/(2(3)/(4))) = -16((-(11)/(2))/((11)/(4))) = -16(-(4)/(2)) = -16\cdot(-2) = 32

User Dimitar Mazhlekov
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.